PERGOLAKAN ANTARA LIFE STYLE DAN SYARI’AT-BUDAYA DALAM KEHIDUPAN PEREMPUAN ACEH MASA KINI - Abdul Wahid (MUWAZAH : jurnal kajian gender, 2013)
Acehnese women life in the demands of the implementation of Islamic law and Aceh cultural context. The development of today's lifestyle demands the women in Aceh to maintain these two patterns. There are a lot of women in Aceh have a strong commitmentto keep the pattern of their life as an "Islamic Acehnese Women", because they believe that the ideal pattern of life among Acehnese women do not leave their roots in the ideal values of Islam and the cultural context. But in many cases, the understanding of thepatterns of live and cultural context of Aceh has been incorrectly interpreted and regarded as part of the teachings of Islam.